Improving the detection of sleep slow oscillations in electroencephalographic data - Dimulescu, Cristiana; Donle, Leonhard; Cakan, Caglar; Goerttler, Thomas; Khakimova, Lilia; Ladenbauer, Julia; Flöel, Agnes; Obermayer, Klaus (Frontiers in Neuroinformatics, 2024)
We aimed to build a tool which facilitates manual labelling of sleep slow oscillations (SOs) and evaluate the performance of traditional sleep SO detection algorithms on such a manually labelled data set. We sought to develop improved methods for SO detection.Method: SOs in polysomnographic recordings acquired during nap time from ten older adults were manually labelled using a custom built graphical user interface tool. Three automatic SO detection algorithms previously used in the literature were evaluated on this data set. Additional machine learning and deep learning algorithms were trained on the manually labelled data set.Results: Our custom built tool significantly decreased the time needed for manual labelling, allowing us to manually inspect 96,277 potential SO events. The three automatic SO detection algorithms showed relatively low accuracy (max. 61.08%), but results were qualitatively similar, with SO density and amplitude increasing with sleep depth. The machine learning and deep learning algorithms showed higher accuracy (best: 99.20%) while maintaining a low prediction time. Conclusions: Accurate detection of SO events is important for investigating their role in memory consolidation. In this context, our tool and proposed methods can provide significant help in identifying these events.